Legal Review of Consumer Protection of Electronic Transactions in Business Law - Andriyani Susilawati; Pandri Zulfikar; Gatot Subroto; Supriadi; M. Ali Akbar; Anharyanto (International Journal of Business and Quality Research, 2026)
The rapid expansion of electronic transactions in Indonesia has fundamentally transformed digital commerce, yet existing consumer protection frameworks remain inadequately equipped to address emerging online risks. This study critically examines the adequacy of Indonesia’s regulatory architecture governing consumer rights in e-commerce, focusing on systemic gaps between traditional legislation and contemporary digital market dynamics. Employing a hybrid juridical-comparative methodology, the research integrates doctrinal analysis of primary legal instruments, comparative benchmarking against EU and US standards, and empirical case review of recent judicial and regulatory decisions. Findings reveal that while foundational regulations such as the Consumer Protection Law (UUPK), Electronic Information and Transactions Law, and Government Regulation No. 80/2019 establish baseline protections, they suffer from critical structural deficiencies. Key impediments include ambiguous platform intermediary liability, fragmented oversight across multiple governmental agencies, the absence of a dedicated Online Dispute Resolution (ODR) mechanism, and administrative sanctions that lack meaningful deterrent effect. Consequently, consumers remain vulnerable to data exploitation, fraudulent practices, and prolonged dispute resolution timelines. To bridge these regulatory gaps, this study recommends the enactment of a specialized digital commerce statute that explicitly defines platform responsibilities, extends withdrawal rights, and mandates algorithmic transparency. Furthermore, the establishment of a cross-institutional coordinating authority and a nationally integrated ODR platform is essential to streamline enforcement and align Indonesia’s consumer protection regime with international best practices. These reforms are crucial for fostering a secure, transparent, and sustainable digital economy.